Antidepressants amitriptyline, fluoxetine, and traditional Chinese medicine Xiaoyaosan caused alterations in gut DNA virome composition and function in rats exposed chronic unpredictable mild stress - Li, Jialin; Qu, Wan; Hu, Chengcheng; Liu, Zongbao; Yan, He (Frontiers in Microbiology, 2023)
In clinical practice, antidepressant drugs are widely used to treat depression, one of the most serious neuropsychiatric diseases, which has also been shown to modulate gut microbial composition or function. Previous studies have attention to the impact of antidepressants on the bacterial microbiome, while the role of these drugs in the gut virome is still unclear. In the present study, we estimated the effects of antidepressant amitriptyline (Ami), fluoxetine (Flu), and traditional Chinese medicine xiaoyaosan (XYS) administration on gut viral composition and function in a chronic unpredictable mild stress (CUMS)-induced depression rat model. The results revealed a significant change in gut viral composition compared with the CUMS-induced rats after treatment with Ami, Flu, and XYS. At the family level, the abundance of f_unclassified_Caudovirales in CUMS rats was remarkably lower than in the HC rats, nevertheless, XYS significantly recovered the abundance of Caudovirales. Meanwhile, the abundance of Podoviridae was expanded in CUMS rats compared with the HC rats, and the profile was then significantly reduced after XYS treatment. Furthermore, both antidepressants and XYS increased the abundance of Siphoviridae compared with the CUMS rats, but only Ami treatments had significant differences. Subsequent function annotation further implied that Ami, Flu, and XYS showed to involve an alteration of the diverse viral functions, such as carbohydrate metabolism, xenobiotics biodegradation and metabolism, community-prokaryotes, translation, and neurodegenerative disease. Additionally, the co-occurrence network displayed that the viral operational taxonomic units (vOTUs) represented by a temperate phage were identified as a complex interaction with the majority of bacterial genera in the intestine ecosystem, inferring that the changes in the gut virome could not be simply accounted for co-variance with altered bacterial hosts. Overall, our study proved for the first time that depression is characterized by massive alterations and functional distortion of the gut viruses, and after oral administration of Ami, Flu, and XYS could affect disordered gut virome, which could be a novel target in depression.